2010
DOI: 10.1007/s12070-010-0111-8
|View full text |Cite
|
Sign up to set email alerts
|

Role of Microsatellites Instability in Carcinogenesis of Postcricoid Carcinoma on Top of Plummer-Vinson Syndrome

Abstract: To develop a molecular pattern that might help in understanding carcinogenesis of postcricoid carcinoma (PCC) on top of Plummer-Vinson syndrome (PVS) in a prospective controlled study. Twenty-four patients with PVS were diagnosed and followed up over a 4 year period, during which eight of them showed malignant change to PCC. Twenty volunteers free of neoplastic diseases were included as a control group. In the two groups, DNA extraction from mononuclear peripheral blood cells, and analysis of loss of heterozyg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…In southern countries where economic resources are limited, cases of PVS are still described [1]- [7].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In southern countries where economic resources are limited, cases of PVS are still described [1]- [7].…”
Section: Discussionmentioning
confidence: 99%
“…In Africa and Asia, cases of PVS are reported in some regions due to poor sociodemographic conditions [1]- [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study by Chisholm, covering a total of 240 PVS patients, 72 being the author’s own series, the long-term follow-up results of these patients revealed that 23 patients developed malignities of the upper digestive system and only 5 (2%) of these patients had oesophageal cancer [ 11 ]. Since not all patients have malignity development, and despite genetic analysis studies for the prediction of cancer development not being covered by routine practices, there are studies on the subject as well [ 12 , 13 ]. Badawy et al suggested in their study that cytogenetic analysis should be performed for PVS patients as a polymorphic marker called CFS1-R, which was detected on the fifth chromosome, was seen in all the cases with post-cricoid cancer [ 12 ].…”
mentioning
confidence: 99%
“…Since not all patients have malignity development, and despite genetic analysis studies for the prediction of cancer development not being covered by routine practices, there are studies on the subject as well [ 12 , 13 ]. Badawy et al suggested in their study that cytogenetic analysis should be performed for PVS patients as a polymorphic marker called CFS1-R, which was detected on the fifth chromosome, was seen in all the cases with post-cricoid cancer [ 12 ].…”
mentioning
confidence: 99%